The Relationship Between Frequency And Breastfeeding Education With The Smoothness Of Postpartum Mother's Breast Milk Production In The Matang Janeng Village Community - Aiman, Ummu; Mukhlisa, Ida (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
The World Health Organization (WHO), United Nation International Children's Emergency fund (UNICEF) and the Ministry of Health recommend initiating breastfeeding within the first hour of a baby's life, exclusive breastfeeding for 6 months, up to 2 years, breastfeeding must be provided together with a safe breastfeeding companion. and nutritious. Production of breastmilk that is not smooth is one of the factors that causes failure in exclusive breastfeeding. One of the efforts to increase breast milk is by breastfeeding children regularly. The purpose of this study was to determine the relationship between the frequency of breastfeeding and the smooth production of postpartum mother's milk in Matang Janeng Village, Tanah Pasir District, North Aceh Regency. This type of research is analytic with cross sectional study design, with a sample of 38 people by total sampling. This research was conducted from 13 to 26 July 2020 with the method of measuring the distribution of questionnaires. Data processing was performed using the chi square test. The results of the univariate analysis showed that the frequency of breastfeeding in postpartum mothers was mostly in the irregular category amounting to 23 people (60.5%) and the milk production of postpartum mothers was mostly in the non-smooth category amounting to 21 people (55.3%) while the results of the analysis bivariate, it was found that there was a relationship between the frequency of breastfeeding and the smooth production of breast milk for postpartum mothers with a p value of 0.003. It is hoped that respondents can breastfeed their babies regularly so that milk production can come out smoothly so that the baby can be fulfilled with nutrition